Susceptibility of acute myeloid leukemia cells to ferroptosis and evasion strategies - Zhang, Hanyun; Sun, Chunjie; Sun, Qi; Li, Ye; Zhou, Chao; Sun, Changgang (Frontiers in Molecular Biosciences, 2023)
Acute myeloid leukemia (AML) is a highly aggressive hematologic malignancy with a five-year survival rate of less than 30%. Continuous updating of diagnostic and therapeutic strategies has not been effective in improving the clinical benefit of AML. AML cells are prone to iron metabolism imbalance due to their unique pathological characteristics, and ferroptosis is a novel cell death mode that is dominated by three cellular biological processes: iron metabolism, oxidative stress and lipid metabolism. An in-depth exploration of the unique ferroptosis mechanism in AML can provide new insights for the diagnosis and treatment of this disease. This study summarizes recent studies on ferroptosis in AML cells and suggests that the metabolic characteristics, gene mutation patterns, and dependence on mitochondria of AML cells greatly increase their susceptibility to ferroptosis. In addition, this study suggests that AML cells can establish a variety of strategies to evade ferroptosis to maintain their survival during the process of occurrence and development, and summarizes the related drugs targeting ferroptosis pathway in AML treatment, which provides development directions for the subsequent mechanism research and clinical treatment of AML. Keywords: ferroptosis, acute myeloid leukemia, iron metabolism, ROS, lipid metabolism Introduction AML is a cancer originating from the hematopoietic stem cell myeloid lineage. It is characterized by the rapid proliferation of primitive cells and their replacement of hematopoietic tissue within the bone marrow, ultimately causing disruption to the normal bone marrow microenvironment. Within this pathological context, hematopoietic progenitor cells undergo clonal expansion, resulting in a blockage of their differentiation and maturation at various stages of development. The incidence of AML has increased annually over the past few decades, and the mortality rate has remained high owing to its aggressive nature and high recurrence rate. Currently, hematopoietic stem cell transplantation (HSCT) and the traditional "3+7" procedure, which was developed in the 1970s, are still used to treat AML. Demethylation medicines, IDH inhibitors, FLT3 inhibitors, and BCL-2 inhibitors are just a few medications that